2015
DOI: 10.1152/ajplung.00256.2015
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled house dust programs pulmonary dendritic cells to promote type 2 T-cell responses by an indirect mechanism

Abstract: The induction of allergen-specific T helper 2 (Th2) cells by lung dendritic cells (DCs) is a critical step in allergic asthma development. Airway delivery of purified allergens or microbial products can promote Th2 priming by lung DCs, but how environmentally relevant quantities and combinations of these factors affect lung DC function is unclear. Here, we investigated the ability of house dust extract (HDE), which contains a mixture of environmental adjuvants, to prime Th2 responses against an innocuous inhal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…The technical difficulties in accurately measuring these cytokines in biological fluids (29,39) might have contributed to the low amounts detected. However, we recently showed that BALF of HDE-treated mice contains an activity that enhances the ability of DCs to direct Th2 differentiation in vitro, and that this activity is independent of IL-33, TSLP, and IL-25 (40). It is possible, therefore, that binding of TNF to its receptor on AECs releases an unidentified factor that contributes to the Th2-promoting activity of lung DCs.…”
Section: Discussionmentioning
confidence: 99%
“…The technical difficulties in accurately measuring these cytokines in biological fluids (29,39) might have contributed to the low amounts detected. However, we recently showed that BALF of HDE-treated mice contains an activity that enhances the ability of DCs to direct Th2 differentiation in vitro, and that this activity is independent of IL-33, TSLP, and IL-25 (40). It is possible, therefore, that binding of TNF to its receptor on AECs releases an unidentified factor that contributes to the Th2-promoting activity of lung DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cDC2s were recently reported to induce Tfh cell responses against inhaled antigens, although this study was performed in the absence of Th2 adjuvants and therefore IgE responses could not be assessed . However, we and others have previously found that lung cDC1s from ID‐exposed mice are capable of stimulating Th2 cell differentiation . Furthermore, both gut and splenic cDC1s have been shown to prime antigen‐specific Tfh cells’ cell responses, raising the possibility that lung cDC1s may do the same under certain conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Because children spend the vast majority of their lives indoors, it is likely that exposures within the home environment influence allergic disease development . Within the home, children are exposed to a variety of immunostimulatory molecules, including allergens and microbial products, which can act as adjuvants in the respiratory tract and promote allergic sensitization to inhaled antigens . While indoor environmental exposures are known to contribute to wheezing and asthma inception in children, there is increasing evidence that the home environment may also impact food allergy development .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations